Care and Weeding of International Agricultural Communications - Allan Deutsch; Christie Anderson (Journal of Applied Communications, 1978)
Eight years ago a gleam in the eye of an Oregon State University agronomist found life when the University established the International Plant Protection Center (IPPC).